Virulência de conídios aéreos e blastósporos de Beauveria Bassiana á broca-do-café, Hypothenemus hampei (Ferrari), em condições laboratoriais - Mota, Marcelo Luiz da (2024)
The growing demand for sustainable farming and pesticide-free food production has driven the development of biological control products. In this study, we aimed to select Beauveria bassiana isolates for controlling H. hampei and assess the pathogenicity of their propagules. Fifteen isolates were collected from naturally infected insects across various municipalities and evaluated for their yield of airborne conidia. The pathogenicity of the airborne conidia and blastospores of these isolates were then tested by applying them to adult female H. hampei using a Potter Tower spray tower at a concentration of 1 x 109. We also assessed the mortality caused by blastospore suspension at various concentrations and liquid fermentation supernatants. The experiments followed a completely randomized design with six replicates per treatment, and each replicate contained ten insects. All isolates demonstrated pathogenicity, with mortality rates ranging from 71.7 to 81.7 and 43.3 to 56.7% for blastospores and airborne conidia, respectively. The supernatants did not cause mortality. The median lethal concentration (CL50) for blastospores was determined to be 1 x 108. The Bv1 and Bv4 isolates exhibited strong pathogenicity and produced airborne conidia comparable with the commercial strain, indicating their potential for use in integrated pest management strategies.